“Evaluación de la lateralidad mediante el test de harris” - Ochoa Maigua, Andrea Liseth (2023)
This research regarding the laterality evaluation by the Harris test was executed diagnosing laterality in children from 5 to 6 years old in the Zumbahua parish, evidencing the ignorance level and the lack of application of the test in the institutions, being the basis for the laterality development at the first-grade students of Basic Education as an important factor in the academic process. Within this research project, the qualitative methodological approach was used, using field and bibliographic research for the collection of information, including the authors perception involved in the laterality evaluation, to verify the academic development carried out by teachers, also the inductive method was used for the observation of the facts generating probable knowledge. The techniques of observation and interview were used to demonstrate teaching strategies applied by teachers for the laterality identification, with the observation sheet based on Harris test activities carried out on a total of 57 children at the first grade of Basic Education, where was determined that the infants are in a locating stage their type of laterality being handled through daily activities carried out in class, sustaining a notable desertion in the teachers before the laterality importance, being necessary that these are handled through trainings, workshops and courses to be implemented in the institutions.